Research on the behavior of certain oilseed rape varieties in Gătaia area - Dragoș Marcela (Agrár- és vidékfejlesztési szemle, 2011)
The study monitored the behavior of some rapeseed varieties in terms of oilseed rape yield and for their introduction in the culture. The study was conducted over a period of three years 2008-2010, in the Gătaia area of Timis county. For testing five varieties of oilseed rape (Alaska, Attila, Triangle, Digger, Milena) were selected .The soil of the experimental field was a vertic-preluvosol, medium clay loam/loam clay on medium fine clays. In the first year of experimentation (2008), the smallest oilseed rape yields have been recorded due to important deviations in this area. Under these conditions the oilseed rape yield ranged between 569 kg/ha and 732 kg/ha. The oilseed rape yield level of the second year of study (2009) ranged between 984 kg/ha and 1142 kg/ha, slightly higher than the previous year. In 2008 the highest oilseed rape yield of 732 kg/ha was obtained from variety Milena, followed by Alaska with a yield of 640 kg/ha, while the lowest oil-seed rape yield (569 kg/ha) was obtained from the variety Digger. In 2009 the highest oilseed rape yield (1149 kg/ha) was obtained from the variety Triangle, and the lowest oil-seed rape crop (984 kg / ha) was obtained from variety Alaska. Research results show that by the introduction of the most suitable varieties in the culture, respecting the fertilizer recovering capacity of the varieties at the determination of the fertilization conditions and respecting the zonal optimum planting period, rape is a crop with real opportunities for expansion in the reference areas.